Preaching Hate: A Critical Study of Charismatic Authority and Its Socio-Political and Socio-Religious Implication - Afzali, Soraya (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Near & Middle Eastern Studies, 2025)
Political regimes and governance systems are imbued with charismatic authority, often associated with individual leaders. However, little attention has been paid to how authority functions in different layers of society, not directly dependent on a particular political leader. This thesis investigates how charismatic authority is a dynamic relationship among individuals, groups, and institutions. Theoretically, this research demonstrates that charisma has both religious and political connotations that function across different layers of society, beginning with an examination of charismatic authority from the perspectives of Persianate and ancient Greece. This highlights the Greek and religious origins of charisma, from which the Weberian theory of charisma has stemmed, and shows the otherworldly characteristics of the notion across different political experiences. The project applies the conceptual framework of charisma to three diverse political regimes and ideologies to observe how the phenomenon provides strategically utilised opportunities for gaining influence, as well as propagating hate, exclusion and marginalisation. Using empirical analysis of material collected through field work, such as in-depth interviews, and secondary qualitative data, the political systems and ideologies of the Taliban in Afghanistan, Khomeinis regime in Iran, and far-right populists in Europe heavily relying on the propagation of hate are analysed. Narratives of hate and processes of othering are amplified though charismatic authority and its dependency on elements of crisis and myth-building as its key components. The experience of displaced communities from Iran and Afghanistan in Europe exemplifies othering and enmity, as they become objects of hostility and hate, shaped by and amplified through the charismatic power relations. Their testimonies resonate with other displaced communities across Europe, adding to a deeper structural and systemic politics of enmity made possible by the instrumental effect of charismatic authority. This dissertation seeks to provide a framework for understanding politico-religious charismatic authority and the way it could contribute to the propagation of hate by exploiting crisis and myth-building and leveraging how identities are formed.
APPROVED
Keywords: Charisma; Authority; Hate; Political Authority; Religious Authority